Job Creation Though Skill Development in India: An Overview: Addressing Skill Shortages for Economic Growth (Journal of Advances and Scholarly Researches in Allied Education, 2018)
A Skilled workforce is an indispensible weapon in the hand of an industrial country to combat the evils of underdevelopment and poverty. Courtiers like China, Japan, Korea, Germany etc. have registered historical successes mainly due to the presence of highly competitive and Skilled workforce. But India in spite of having a huge population of young workers fails to gain the momentum of growth, although uncountable jobs are looming ahead. The problem lies in skill deficient workforce of India. The present paper is an attempt to bring out the needs of skill enhancement program and steps taken by the government and other agencies to combat the problems related to the skill shortages.